2011
DOI: 10.3389/fmicb.2011.00032
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Escherichia Coli O157:H7 by Bovine Rectal Epithelial Cells

Abstract: Escherichia coli O157:H7 (O157) causes human diarrheal disease and healthy cattle are its primary reservoir. O157 colonize the bovine epithelial mucosa at the recto-anal junction (RAJ). Previous studies show that O157 at this site are not eliminated by aggressive interventions including applications of O157-specific lytic bacteriophages and other bactericidal agents. We hypothesize that some O157 at the RAJ mucosa are protected from these killing agents by host cell internalization. To test this hypothesis, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…In addition, Sheng et al . () demonstrated that intimin–Tir interaction was not required for efficient EHEC O157:H7 invasion of primary bovine epithelial cells. Furthermore, other effector proteins were associated with EPEC invasion in vitro , such as Map (Jepson et al ., ), EspF (Weflen et al ., ), and EspT (Bulgin et al ., , b), that manipulate Rho‐GTPase signaling pathways (reviewed in Wong et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sheng et al . () demonstrated that intimin–Tir interaction was not required for efficient EHEC O157:H7 invasion of primary bovine epithelial cells. Furthermore, other effector proteins were associated with EPEC invasion in vitro , such as Map (Jepson et al ., ), EspF (Weflen et al ., ), and EspT (Bulgin et al ., , b), that manipulate Rho‐GTPase signaling pathways (reviewed in Wong et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although LEE-encoded effector proteins might play a role in gut colonization (Naylor et al, 2005;Vlisidou et al, 2006;Dziva et al, 2007), LEE-negative STEC strains can colonize cattle efficiently, showing that other factors influence the persistence of STEC in the bovine intestine. Sheng et al (2011) working with rectal biopsies and with primary bovine rectal epithelial cell (PBRE) cultures, showed that a subpopulation of STEC O157 : H7 was internalized, and that deletion of the tir gene, although impairing the intimate attachment and production of A/E lesions, did not affect bacterial internalization of the strain EDL933. Electron micrographs taken from infected PBRE cells showed microvilli-like membrane extensions surrounding the internalizing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, work seeking to explain the bacterial colonization of the bovine intestinal mucosa by STEC moved from the role played by bacterial adhesins to the investigation of STEC invasiveness (Sheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, only two studies have considered the role of cellular immunity during EHEC O157:H7 colonization in ruminants; these identified lymphoproliferative cellular responses to heat-killed EHEC O157:H7 (40) and recombinant antigens (41) in bovine peripheral blood mononuclear cells and ovine rectal lymph node cells, respectively. The case for a protective cellular immune response is further strengthened by the observations that colonized bovine epithelial cells are exfoliated in vivo (42) and that some strains are efficiently internalized by bovine epithelial cells both in vivo and in vitro (43).…”
mentioning
confidence: 99%